Comparison of proposed arc model for power circuit breakers against the Cassie Mayr's models: article - Mat Palal, Mohd Ozahir (2008)
This paper address the possibility of designing and describes a comparison between Mayr's and Cassie's arc models and proposed model during contact separation of circuit breaker by using Matlab Simulink. This design of the propose model has been simulated in MATLAB Simulink. The design of proposed model successfully made. Through the simulation made, simulation results of several contact separation time, arc voltage, time interval of arc and post arc current zero was determine. This result found and compare to the Mayrís and Cassie arc model. This project it is a successful because if compared to exist model, the results approximately close from the proposed arc model.